Factors Influence Adherence Treatment Drugs-Resistant Tuberculosis Client - Priyo Purnomo As'hab; Budi Anna Keliat (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
The success rate of drug-resistant tuberculosis treatment in the world is still low. Success rates are affected by medication adherence, while loss to follow-up (LTFU) is still found in patients with drug-resistant tuberculosis. It is important to know the factors that influence adherence to make an effort to increase the success rate of drug resistant tuberculosis treatment. The aim is to systematically identify the factors that influence adherence that result in treatment failure in patients with drug-resistant tuberculosis. Systematic reviews are used by searching online database articles (EBSCO Hosts, Clinical Keys, SAGE Publications, and Science Direct). The keywords used are